Time to achieve a patient acceptable symptom state in myasthenia gravis - Martinez-Harms, Rodrigo; Barnett, Carolina; Bril, Vera (Frontiers in Neurology, 2023)
Abstract Introduction: The patient acceptable symptom state (PASS) is a reliable way to characterize a patient’s satisfaction with their disease state in a “Yes”/“No” dichotomous manner. There is limited data on the time required to reach an acceptable state in Myasthenia Gravis (MG). We aimed to determine the time to reach a first PASS “Yes” response in patients at MG diagnosis and a PASS “No” status, and also to determine the influence of various factors on this time. Methods: We performed a retrospective study of patients diagnosed with myasthenia gravis who had an initial PASS “No” response and defined the time to reach a first PASS “Yes” by Kaplan-Meier analysis. Correlations were made between demographics, clinical characteristics, treatment and disease severity, using the Myasthenia Gravis Impairment Index (MGII) and Simple Single Question (SSQ). Results: In 86 patients meeting inclusion criteria, the median time to PASS “Yes” was 15 months (95% CI 11-18). Of 67 MG patients who achieved PASS “Yes”, 61 (91%), achieved it by 25 months after diagnosis. Patients who required only prednisone therapy achieved PASS “Yes” in a shorter time with a median of 5.5 months (P = 0.01). Very-late-onset MG patients reached PASS “Yes” status in a shorter time (HR= 1.99, 95% CI 0.26-2.63; p=0.001). Discussion: Most patients reached PASS “Yes” by 25 months after diagnosis. MG patients who only required prednisone and those with very-late-onset MG reach PASS “Yes” in shorter intervals.